Integrative learning experience with the Division of Food Safety and Lodging at the Kansas Department of Agriculture and the international mobility of veterinary students program in Italy - Armstrong, Marie (My University, 2019)
This report summarizes the Integrative Learning Experience (ILE) that the student pursued at the University of Padova (UNIPD) in Italy, and the Kansas Department of Agriculture (KDA) in Manhattan, Kansas. The two-week International Mobility of Veterinary Students (i-MOVES) program was organized by professors at the UNIPD. The students attended practicums, lectures, and field trips in the Food Safety, Public Health and Animal Welfare realm. During the i-MOVES program, the student visited the headquarters of an international seafood processing company, a commercial poultry farm, and a modern beef slaughter facility. The trip to Italy gave the student an opportunity to explore beyond the i-MOVES program to observe distinctive items that were prominent to the ILE experience. In the span of six months, a KDA Division of Food Safety and Lodging internship gave the student the opportunity to work as a Hazard Analysis and Critical Control Points (HACCP) Specialist Intern. Her role involved the development of HACCP plans, the documentation of food complaints, and sanitarian assignments for investigations of food establishments. In addition to the internship, she participated in the annual Emergency Preparedness Exercise, RAMPART, as the Database Technical Specialist at the KDA. Participating members of the RAMPART exercise included KDA professionals, the U.S. Department of Agriculture (USDA), the U.S. Department of Homeland Security (DHS), the USDA Animal and Plant Health Inspection Service Veterinary Services (APHIS-VS), and several state departments of agriculture. This ILE report describes the knowledge and skills gained throughout the Master of Public Health program and how it was applied during the student’s field experience in Italy and at the KDA.
Keywords: food safety; HACCP; KDA; Italy; RAMPART; i-MOVES